Outcomes from the key inquiries and the evolution of modern forensic psychiatry - Murray, Kevin (Seminars in forensic psychiatry, 2024)
This chapter offers an account of the key events shaping modern forensic psychiatry since the 1950s, including legal reforms, political initiatives and key reports which have influenced practice. These are summarised in a narrative beginning with the 1959 Mental Health Act and concluding with the most recent Wessely proposals for reform. The critical clinical events including the cases of Graham Young, Peter Sutcliffe, Christopher Clunis and Michael Stone, the Carstairs escapes and the Butler, Reed, Blom-Cooper, Fallon and Tilt reports are discussed. The chapter includes a commentary on the development of medium-secure services and the refocussing of high-secure care since 2000.